Analisis Peranan Kantor Urusan Agama (KUA), Pernikahan Dini dan Faktor Ekonomi pada Angka Perceraian di Kantor Urusan Agama Kabupaten Bogor - Raden Muhammad Jiddan Aziz; Anwar Rahim; Arif Rachman Shaleh; ndupurnahayu ndupurnahayu (Publikasi Indonesia, 2022)
The object of this research is residents who are recorded in marriage at the KUA Bogor Regency and several samples are taken to determine the divorce rate caused by underage marriages. Y) is very significant. Techniques for collecting data were using a questionnaire given to the community who had been recorded in carrying out marriages at the KUA in Bogor district, especially tajur halang as many as 194 people. Analysis of the role of employees at KUA that the influence of early marriage variables on the divorce rate is very strong.